If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 11 = 9 Reorder the terms: 11 + 2c = 9 Solving 11 + 2c = 9 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 2c = 9 + -11 Combine like terms: 11 + -11 = 0 0 + 2c = 9 + -11 2c = 9 + -11 Combine like terms: 9 + -11 = -2 2c = -2 Divide each side by '2'. c = -1 Simplifying c = -1
| .50z+0.2=.15z-10.5 | | 9x+25=3x+157 | | 2x+11=-9 | | 4x+13=-52+9x | | y=16x^2+40x+32 | | 2v^2=-7v-5 | | x+3x+x+300=1100 | | 40y+4+60y=2 | | 4+6w=2 | | 2w^2+5w=-3 | | 3x+7=70-60x | | -3(2x+6)=-12 | | 7x-4y=-29 | | 2a+10+5a-2= | | t+8m+4t-4m= | | 8q+10q+14= | | .40y+4+.60y=2 | | 8y+12y+3y= | | 5a+6a-9a= | | 3x-5y=-24 | | 6x=5+1 | | q+9+2q+5q= | | 5r-10r+8rs= | | 19y-10= | | 5t+7t-1= | | 12rt-10r+18t= | | 18+k=8 | | (10b-9)-3(3b+3)=-3 | | E^1/2x=1/2 | | y-0.06y=29546773 | | (10b-9)-3(3b+3)=3 | | s+14=p |